Elevated cholesteryl ester transfer protein (CETP) activity, a major determinant of the atherogenic dyslipidemia, and atherosclerotic cardiovascular disease in South Asians. (29th August 2020) - Rashid, Shirya; Sniderman, Allan; Melone, Michelle; Brown, Patrick E; Otvos, James D; Mente, Andrew; Schulze, Karleen; McQueen, Matthew J; Anand, Sonia S; Yusuf, Salim
Abstract: Aims: Why South Asians are at increased risk of premature atherosclerotic cardiovascular diseases compared with other ethnic groups is not fully understood. Atherogenic dyslipoproteinemia – hypertriglyceridemia, elevated numbers of low-density lipoprotein (LDL) particles and low high-density lipoprotein cholesterol (HDL-C) – is more common in South Asians but the mechanisms responsible have not been explicated. Here we examined whether the circulating lipid transfer protein, cholesteryl ester transfer protein (CETP), plays a role in the pathogenesis of the atherogenic dyslipoproteinemia among South Asians. Methods and results: CETP activity was determined by exogenous substrate assay in the serum of healthy, metabolically well-characterized individuals of South Asian and European descent ( N  = 244 and 238, respectively). Serum and lipoprotein lipids and apolipoproteins were measured and lipoprotein particle number and size were quantified via nuclear magnetic resonance spectroscopy. All the elements of the atherogenic dyslipoproteinemia were more severe in South Asians and CETP activity was significantly greater by 30% in South Asians compared with Europeans, adjusted for age, sex, body mass index and waist circumference ( p  < 0.0001). CETP activity was directly associated with serum triglycerides and inversely with HDL-C in the whole population. CETP activity was also directly related to apoB and LDL particle number. Finally, increased CETP activity was associated with pro-atherogenic reductions in HDL and LDL particle size. Conclusions: We identified novel associations between elevated CETP activity and the triad of quantitative and qualitative lipoprotein abnormalities in the atherogenic dyslipidemia in South Asians, a major contributor of increased atherosclerotic cardiovascular diseases in South Asians.